Pengembangan Aplikasi Exampro Sebagai Model Evaluasi Pembelajaran Berbasis Digital - Ashadi, Ninik Rahayu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this Study is to find out How the development of the Exampro app as a digital-based learning evaluation model resulted. The method of this study is This research uses a Research and Development/R&D approach with a modified Borg & Gall model of development. This model consists of ten steps, however in this study it is simplified to six main stages, namely: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product testing. Research Results (1) based on the validation assessment of the Subject Matter Expert showed a feasibility score of 88%, falling into the